2016
DOI: 10.1007/82_2016_32
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus-Associated Skin and Soft Tissue Infections: Anatomical Localization, Epidemiology, Therapy and Potential Prophylaxis

Abstract: Skin and soft tissue infections (SSTIs) are among the most common infections worldwide. They range in severity from minor, self-limiting, superficial infections to life-threatening diseases requiring all the resources of modern medicine. Community (CA) and healthcare (HA) acquired SSTIs are most commonly caused by Staphylococcus aureus . They have variable presentations ranging from impetigo and folliculitis to surgical site infections (SSIs). Superficial SSTIs may lead to even more invasive infections such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 146 publications
3
53
0
1
Order By: Relevance
“…The observation that all MRSA isolates were susceptible to linezolid is similar to reports from other countries that MRSA isolates were susceptible to linezolid [20,22,25] . In addition, the MIC distribution of the glycopeptide antibiotics showed that the majority ( ∼ 97%) of the isolates were susceptible to vancomycin and teicoplanin (MIC: ≤ 2 μg/ml), confirming that vancomycin and teicoplanin remain viable options for treating MRSA infections in Kuwait.…”
Section: Discussionsupporting
confidence: 76%
“…The observation that all MRSA isolates were susceptible to linezolid is similar to reports from other countries that MRSA isolates were susceptible to linezolid [20,22,25] . In addition, the MIC distribution of the glycopeptide antibiotics showed that the majority ( ∼ 97%) of the isolates were susceptible to vancomycin and teicoplanin (MIC: ≤ 2 μg/ml), confirming that vancomycin and teicoplanin remain viable options for treating MRSA infections in Kuwait.…”
Section: Discussionsupporting
confidence: 76%
“…and general (innate or acquired deficiencies of the immune system such as complement system deficiencies, granulocytopenia, agranulocytosis, AIDS, diabetes, immunosuppressive treatments, etc.). It is able to cause a plethora of community (CA) and health care (HA) infections, ranging from superficial skin infections to severe, and potentially fatal, invasive diseases [3][4][5] due to its ability to produce a spectrum of virulence factors and resistance to multiple antibiotics, frequently encoded by mobile genetic elements (MGEs) [6], which have eased the persistence of S. aureus in hospital environment [7]. S. aureus is causing skin and soft tissue infections (SSTIs), endovascular infections, pneumonia, septic arthritis, endocarditis, osteomyelitis, foreign-body infections, and sepsis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one third of the entire human population worldwide is asymptomatically colonized by S. aureus , which mainly inhabits epithelial surfaces (Missiakas and Schneewind, 2016). However, under certain circumstances, this bacterium can eventually become a life-threatening pathogen causing infections in skin and soft tissues, sepsis, endocarditis, osteomyelitis, pneumonia, and toxic shock syndrome (David and Daum, 2010; Olaniyi et al, 2016). S. aureus is responsible for infections both in the healthcare setting and in the community and, also due to its impressive capacity to develop antibiotic resistance, constitutes a major burden on human society (Monaco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%